Limited impact of business development programs on profitability in the presence of ambiguity aversion - Dmitry Shapiro (Asian Development Bank (ADB), 2020)
This paper develops a theoretical framework to explain the limited effect of business development programs (BDPs) on entrepreneurs' profits. We argue that a mismatch between a BDP's narrow focus on business-promoting strategies and the wider context in which microentrepreneurs operate can limit the impact of business training. In our framework, entrepreneurs are ambiguity averse and have multiple sources of income (e.g., business and wage incomes). We show that for a sufficiently ambiguity-averse entrepreneur with multiple income sources, efficient training can result in a decline in expected profit. Notably, when the wider context (multiple income sources, ambiguity aversion) is considered, the business training impact is limited and can result in a posttraining expected profit decline. This limited impact is caused by the diversifying role that the business income plays in household finances.
Keywords: D10; O12; O16; 330; ambiguity aversion; business development programs; microentrepreneurship